Dissolution Kinetics of Thermally Dehydrated Colemanite in Perchloric Acid Solutions - KUBILAY, S.; YALCINKAYA, Z.; ALKAN, S.; SAVRAN, A. (Asian Journal of Chemistry, 2010)
In this study, the dissolution of thermally dehydrated colemanitein aqueous perchloric acid solutions was investigatedin a batch reactor employing the parameters of solid to liquidratio, particle size, temperature and acid concentration. It wasfound that the dissolution rate increased with increasingtemperature and acid concentration, decreasing particle sizeand solid to liquid ratio. No important effect of stirring speedwas observed. The dissolution kinetics of colemanite wasexamined according to heterogeneous and homogeneousreaction models and it was found that the dissolution ratewas controlled by heterogeneous chemical reaction. Theactivation energy of the process was determined to be 41.07kJ mol-1. The experimental data were tested by graphical andstatistical methods and it was found that the following modelbest fit the experimental data1 - (1-X)1/3 = 7.56 × 105 (Rp)-0.1076 × (CA)0.4629 × (S/L) -0.2525 × e-4938.7/T × t